Seasonal and Gender Differences in Presence of Rickettsia felis and Blood meals Provide Additional Evidence of a Vector Role for Mosquitoes - Jilei Zhang; Guangwu Lu; Patrick John Kelly; Chengming Wang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Rickettsia felis belongs to spotted fever group Rickettsia and is an emerging human pathogen most commonly transmitted by a range of fleas and ticks. While recent evidence has suggested mosquitoes are infected with R. felis, there is little information about the role of mosquitoes in the organism’s transmission. In this study, around 100 mosquitoes were collected monthly between 2013 and 2014 from the same residential dwelling at Yangzhou, China. The collected mosquitoes were identified for their species and gender, followed by gltA-based PCR and hydroxymethylbilane synthase-based PCR to determine the prevalence of Rickettsia and blood meal. Three mosquito species (Culex pipiens: 76%, 996/1,304; C. tritaeniorhynchus: 17%, 216/1,304; Aedes albopictus: 7%, 92/1,304) were identified. For 1,088 female mosquitoes, 31% of them n=336 were positive for blood meal and 7% n=77 carried R. felis DNA. In a strong contrast, none of the 216 male mosquitoes were positive for blood meal but two males were positive for Rickettsia. Interestingly, 63% of R. felis-positive mosquitoes (50/79) were negative for blood meal, being significantly higher than 37% of mosquitoes and being positive for both R. felis and blood meal P=0.008. Furthermore, we compared the prevalence of Rickettsia and blood meal in the mosquitoes collected in the months with temperature below and above 23°C, the minimum temperature required for mosquito egg hatching. Mosquitoes captured in the months below 23°C showed significant higher positivity of R. felis(71/936, 7.6% vs. 8/368, 2.2%; P=0.002) and blood meal (294/936, 31.4% vs. 36/368, 9.8%; P<10−4) than in the months above 23°C. Collectively, the seasonal and gender differences of R. felis and blood meal in mosquitoes add to the existing evidence, supporting a potential vector role of mosquitoes in the transmission of R. felis. Studies with a R. felis infection model covering the full life cycle of mosquitoes is necessary to unambiguously prove the transstadial and transovarial transmission of R. felis in mosquitoes.